Tingkat Pengetahuan WUS dengan Keikutsertaan Tes IVA sebagai Upaya Deteksi Dini Kanker Serviks - Putu Indah Sintya Dewi; Luh Ayu Purnami; Putu Agus Ariana; Ni Komang Ayu Arcawati (Journal of Telenursing (JOTING), 2021)
This study aims to determine and analyze the relationship between the level of knowledge and the participation of fertile aged women (WUS) in the visual inspection of acetic acid (IVA). This study used an analytic survey method with a cross-sectional approach. The analysis results using the Chi-Square test showed that the p-value was 0.001 (p<ɑ 0.005). In conclusion, there is a relationship between the level of knowledge and the participation of WUS in the visual inspection of acetic acid in the working area of the UPTD Puskesmas Blahbatuh II. Keywords: Acetic Acid Visual Inspection, Participation, Knowledge